2017
DOI: 10.1177/0363546517744219
|View full text |Cite
|
Sign up to set email alerts
|

Do Selective COX-2 Inhibitors Affect Pain Control and Healing After Arthroscopic Rotator Cuff Repair? A Preliminary Study

Abstract: Despite having similar postoperative analgesic effects as other nonsteroidal anti-inflammatory drugs and opioids, selective COX-2 inhibitors should not be used for postoperative analgesia because they might negatively affect tendon-to-bone healing after surgical repair. Registration: NCT02850211 ( ClinicalTrials.gov identifier).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 41 publications
1
51
0
1
Order By: Relevance
“…However, adverse side effects caused by oral medications are an annoying problem. Opioid drugs could result in nausea, sedation, constipation, vomiting, and respiratory depression [ 8 ]. On the other hand, due to inhibition of cyclooxygenase (COX)-1 and disturbance of platelet function, traditional nonselective NSAIDs might lead to gastrointestinal toxicity and bleeding [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, adverse side effects caused by oral medications are an annoying problem. Opioid drugs could result in nausea, sedation, constipation, vomiting, and respiratory depression [ 8 ]. On the other hand, due to inhibition of cyclooxygenase (COX)-1 and disturbance of platelet function, traditional nonselective NSAIDs might lead to gastrointestinal toxicity and bleeding [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soreide et al 24 used diclofenac, ketorolac, celecoxib, or another NSAID for a mean of 6.7 days but did not report the dosage. Oh et al 21 compared celecoxib (200 mg twice a day) versus ibuprofen (385 mg 3 times a day) administered for 14 days after treatment. Blomquist et al 3 did not report the specific NSAID used or the dosage but noted that the NSAID was administered for an interval ranging from 1 to 7 days postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…The reported surgical failure rate among control participants who were not given NSAIDs was 3.7% (147/3996). Surgical failure rates among patients administered NSAIDs for each procedure were as follows: meniscal repair, 34% (11/32) 22 ; ACL reconstruction, 3% (127/4144) 24 ; rotator cuff repair, 23% (celecoxib 11/30 and ibuprofen 2/27) 21 ; and Bankart repair, 5% (6/127). 3 NSAID use showed no statistically significant effect on need for reoperation after meniscal repair ( P = .99), ACL reconstruction ( P = .8), and Bankart repair ( P = .8) compared with no NSAID administration.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, selective COX-2 inhibitors were associated with fewer gastrointestinal side effects than non-selective COX-2 inhibitor. A preliminary study by Oh et al [36], the efficacy of a selective COX-2 inhibitor in early postoperative pain control, pain management satisfaction level, and incidence of systemic adverse effects in patients undergoing arthroscopic rotator cuff repair were evaluated. This study concluded that, although the selective COX-2 inhibitors have similar postoperative analgesic effects as other nonsteroidal anti-inflammatory drugs and opioids, they might negatively affect tendon-to-bone healing after surgical repair, and thus, they should not be used for postoperative analgesia.…”
Section: Discussionmentioning
confidence: 99%